2015
DOI: 10.1089/scd.2015.0138
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Wharton's Jelly and Bone Marrow-Derived Mesenchymal Stromal Cells to Enhance Engraftment of Cord Blood CD34+Transplants

Abstract: Cotransplantation of CD34+ hematopoietic stem and progenitor cells (HSPCs) with mesenchymal stromal cells (MSCs) enhances HSPC engraftment. For these applications, MSCs are mostly obtained from bone marrow (BM). However, MSCs can also be isolated from the Wharton's jelly (WJ) of the human umbilical cord. This source, regarded to be a waste product, enables a relatively low-cost MSC acquisition without any burden to the donor. In this study, we evaluated the ability of WJ MSCs to enhance HSPC engraftment. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…In the past decade, many basic studies showed the brilliant results of MSC-based therapeutic plans, including myocardial infarcts [32], diabetes [33], neurological disorders [5,7], and GVHD [7,12]. In addition, MSCs exhibit therapeutic potential for diverse diseases, including Osteogenesis imperfecta [10], GVHD [1113], myocardial infarction [14,15], Crohn’s disease [16], alcoholic cirrhosis [17], and amyotrophic lateral sclerosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, many basic studies showed the brilliant results of MSC-based therapeutic plans, including myocardial infarcts [32], diabetes [33], neurological disorders [5,7], and GVHD [7,12]. In addition, MSCs exhibit therapeutic potential for diverse diseases, including Osteogenesis imperfecta [10], GVHD [1113], myocardial infarction [14,15], Crohn’s disease [16], alcoholic cirrhosis [17], and amyotrophic lateral sclerosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method is based on the capacity of MSCs to adhere to plastic surfaces [2,33]. After 3-day culture in a humidified incubator at 37°C and 5% CO 2 , the non-adhering cells were washed from the flask using PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Besides de abovementioned advantages, hWJMSCs, have an enhanced expression of neurotrophic factors, and a spontaneous tendency toward a neural lineage differentiation compared to MSCs isolated from adult tissues 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the mesenchymal stem cells belongs to important therapeutic strategies in hematologic transplantology. Adjuvant transplant of umbilical cord MSCs was shown to facilitate engraftment of the transplant of the bone marrow, peripheral and cord blood [31,32,33,34]. Due to outstanding immunosuppressive properties umbilical cord mesenchymal stem cells are also increasingly used in the treatment of the graft-versus-host disease [51].…”
Section: Application Of the Umbilical Cord Mscs In The Treatment Of Imentioning
confidence: 99%
“…• Availability, cost-effectiveness, ethics and simplicity of obtaining [1,4,13 [13,32,33,34]; • Effective medium for the culture of other cell populations [6,14];…”
mentioning
confidence: 99%